Innovation in Human Resource Management: Building an Adaptive and Inclusive Work Culture at PT.Agro Niaga Abadi - Rudi Suprianto Ahmadi; Dodi Tisna Amijaya; Rakhmia Nalibratawati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to conduct a comprehensive analysis of innovations in human resource management (HRM) instituted by PT. Agro Niaga Abadi, with the aim of fostering an adaptive and inclusive organizational culture. The methodology used in this study is qualitative, utilizing a case study framework that combines extensive interviews with human resource development (HRD) managers, department leaders, and direct observation techniques within the company environment. The findings of this investigation reveal that PT. Agro Niaga Abadi has successfully implemented various innovative practices in HRM, including the adoption of digital recruitment methodologies, progressive training initiatives, and competency-based performance evaluations. In addition, the organization has effectively fostered an adaptive work culture through the implementation of internal innovation projects, the facilitation of regular deliberation forums, and the provision of adaptive leadership training programs. Initiatives aimed at building an inclusive work culture are exemplified by the implementation of equality policies and the guarantee of fair access to career advancement opportunities for all personnel. However, the organization faces several barriers, including resistance to transformative change, constraints in digital infrastructure, and the need for continuing education training.